Strategi Pengembangan Agribisnis Peternakan Sapi Perah Di Kabupaten Kediri - Istar Abadi (Manajemen Agribisnis: Jurnal Agribisnis, 2019)
Dairy Cattle Raising livestock in Kediri as a dairy farm development areas in East Java is still a small-scale businesses. The level of production, the level of consumption, the origin of milk protein needs can not be fulfilled optimally, although natural resources support. Therefore, a dairy farm in Kediri is still possible to develop the necessary strategy and development of effective and efficient. The purpose of this study, among others, is to establish the region as an area representative dairy farm agribusiness development, establish appropriate strategies for the development of agribusiness dairy farm as well as to arrange alternative agribusiness development strategy dairy farm in Kediri. Research using primary and secondary data types. Primary data collection techniques for interviews, direct interviews and questionnaires with respondents specialists/experts and entrepreneurs (dairy farmers). Analytical techniques used include the analysis of LQ (Location quation), AHP (Analytical Hierarchy Process) and SWOT analysis. LQ analysis results showed the District of Ngancar adequate as agribusiness development area dairy farm with a second buffer area in District Kandangan. The appropriate strategy is growth stability (stability of growth) through horizontal integration strategy for improved economies of scale. Alternative strategies for the development of agribusiness dairy farm are: 1). S-O Strategies (Strength-Opportunity) which is to increase the number of dairy cow population through the conclusion of joint venture or partner with another party patterns, expand markets, improve production facilities and technology, optimize land and increase the types of dairy products; 2). Strategy W-O (Weakness- Opportunity) that creates unity and container farmer groups, improve product processing, making the central areas of quality dairy cows, the increase in feed processing and increase sales promotion; 3). Strategy S-T (Strength-Treath) that increased adoption of technological innovation, empowerment of farm credit by farmers, community empowerment in the dairy cattle business, enhance the competitiveness of milk products and the application of quality assurance and food safety at pengohahan livestock products; 4). Strategy W-T (Weakness -Treaths), namely recruitment, upgrading and development of the role of technical facilitator breeding and selecting distribution channels marketing of primary products fresh milk dairy cows. To improve the effectiveness of the strategy has been formulated needed prioritized intervention to these strategies is a priority. In addition, institutional management for the development of agribusiness dairy farm systems need to be identified and carefully engineered so that the strategy adopted to encourage the achievement of the goal of developing agribusiness dairy farm in Kediri.